2019
DOI: 10.1186/s12916-019-1353-2
|View full text |Cite
|
Sign up to set email alerts
|

Automated versus physician assignment of cause of death for verbal autopsies: randomized trial of 9374 deaths in 117 villages in India

Abstract: Background Verbal autopsies with physician assignment of cause of death (COD) are commonly used in settings where medical certification of deaths is uncommon. It remains unanswered if automated algorithms can replace physician assignment. Methods We randomized verbal autopsy interviews for deaths in 117 villages in rural India to either physician or automated COD assignment. Twenty-four trained lay (non-medical) surveyors applied the allocated method using a laptop-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
1
22
2
Order By: Relevance
“…15 A second publication evaluated the causes of all deaths in adults and children, comparing physicianassigned cause of death at tertiary hospitals involved in final care with InterVA4 and InterVA5, which found high concordance (eg, InterVA5 correlation coefficient of 0•86 [0•79-0•93] for adults). 6 InterVA4 has been compared with physician review for deaths in general [16][17][18][19] and for maternal death specifically. 20 In Africa and Asia among adults or the general population, concordance between physician review and InterVA4 has been variably reported, as high (≥80%) 17,18 or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A second publication evaluated the causes of all deaths in adults and children, comparing physicianassigned cause of death at tertiary hospitals involved in final care with InterVA4 and InterVA5, which found high concordance (eg, InterVA5 correlation coefficient of 0•86 [0•79-0•93] for adults). 6 InterVA4 has been compared with physician review for deaths in general [16][17][18][19] and for maternal death specifically. 20 In Africa and Asia among adults or the general population, concordance between physician review and InterVA4 has been variably reported, as high (≥80%) 17,18 or not.…”
Section: Discussionmentioning
confidence: 99%
“…6 InterVA4 has been compared with physician review for deaths in general [16][17][18][19] and for maternal death specifically. 20 In Africa and Asia among adults or the general population, concordance between physician review and InterVA4 has been variably reported, as high (≥80%) 17,18 or not. 16,19,21 Among 86 maternal deaths analysed at the healthfacility level in Malawi, fair to good agreement was reported between an expert physician review panel and InterVA4 for ICDMM categories 1-7 (Cohen's κ=0•66), although the expert physician review panel assigned cause of death as unspecified more often than both InterVA4 and InterVA5.…”
Section: Discussionmentioning
confidence: 99%
“…We applied chance-corrected mortality fraction accuracy to calculate the population-level concordance between the NBE and GBD, taking into account chance agreement. 20 100% concordance would mean identical cause of death distribution in the two comparisons. The major source of uncertainty in the NBE does not arise from random errors: the sample size for the MDS is very large and completeness of the sources of vital rates is high, as evaluated independently by the UN.…”
Section: Discussionmentioning
confidence: 99%
“…17 Earlier evaluations of the MDS have shown high comparability with relevant hospital or clinical data, strong reproducibility of the dual physician-coded verbal autopsies, and generally low rates of misclassification in children and young and middle-age adults. 15,16,20 Moreover, the uncertainty in diagnosis on verbal autopsy is not likely to affect the relative ranking of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, to improve population health for these (mostly) rural communities where most deaths occur at home, efficient mortality reduction strategies require reliable COD information systems, and the only viable means to do so is the routine use of automated VA. It is simply not imaginable that requiring busy rural physicians to do so on a regular basis is sustainable, despite claims to the contrary [36]. Our experience under the D4H Initiative in more than a dozen countries suggests that reliable methods such as SmartVA can readily, cost-effectively and in a timely fashion yield the essential information needed to guide public policy [14,15].…”
Section: Discussionmentioning
confidence: 99%